Influence of Rhizobium phaseoli Inoculation and Phosphorus Application on Nodulation and Yield of two Dry Bean (Phaseolus vulgaris) Cultivars - Ndlovu, Tshepo John; Mariga, Irvine Kwaramba; Mafeo, Tieho Paulus (Internal Journal of Agriculture and Biology, 2017)
Two field experiments were conducted to investigate the response of dry bean cultivars to inoculation and phosphorus application under dryland farming conditions during two summer growing seasons at the Syferkuil farm of University of Limpopo. The experiments were split split-plot arrangements in randomized complete block design with four replications. The main plot factor comprised of two dry bean cultivars viz, red speckled bean and small white haricot. Rhizobium phaseoli inoculation levels (inoculated and uninoculated) were assigned in the sub-plot whilst the sub-sub plot was applied with three phosphorus rates at 0, 45 and 90 kg P kg/ha. There was no interactive effect of treatment factors on nodulation and most yield parameters. In 2011/2012 growing season nodulation was not significantly different between the two cultivars, but in 2012/2013 season the red speckled bean achieved significantly higher number of nodules per plant and nodule dry weight. Inoculation with R. phaseoli resulted in increased nodulation in 2012/2013 season. Cultivar significantly affected 100 seed weight, grain yield and total above ground biomass in both growing seasons. The red speckled bean produced higher grain yield of 1657 kg/ha and 2547 kg/ha in 2011/2012 and 2012/2013, respectively. In contrast, the small white haricot bean achieved grain yield of 1396 kg/ha and 1797 kg/ha in the respective seasons. Grain yield was significantly increased by approximately 16.15 and 27.50% with Rhizobium inoculation in the respective seasons. Phosphorus application at varying rates did not have a significant (P ≤ 0.05) influence on all parameters measured in the experiment during both growing seasons. © 2017 Friends Science Publishers
Journal article published in the International Journal of Agriculture and Biology, vol.19, no. 6, 2017
Keywords: Cultivar; Rhizobium; Inoculation; Phosphorus; Nodulation; Rhizobium; Crops -- Inoculation